Tribological properties of bacterial cellulose in reciprocating sliding against bovine articular cartilage - Lopes, J. L. (2010)
Bacterial cellulose (BC) is a biocompatible material with unique properties, such as high water holding capacity, ultra-fine fibre network and high strength that makes it an attractive material for the repair of articular cartilage lesions. However, data on the tribological properties of BC is very scarce, particularly if natural articular cartilage is involved in the contact. In this work, BC was grown statically and its tribological properties were investigated by reciprocating sliding against bovine articular cartilage, in the presence of a simulated synovial fluid, under different normal applied loads. Low friction coefficient values were obtained, ranging from 0.04 to 0.06, and preservation of the surface integrity of BC after sliding under contact pressure up to 2.4 MPa, which confirms the potential of this gel to be used as artificial cartilage for articular joints.